Exercise-related cognitive effects on sensory-motor control in athletes and drummers compared to non-athletes and other musicians. (30th September 2017) - Bianco, V.; Berchicci, M.; Perri, R.L.; Quinzi, F.; Di Russo, F.
Highlights: Brain plasticity to visuo-motor skills differs in drummers and no-drummer musicians. Playing sport and drums lead to similar benefits at behavioral and cognitive level. The benefits of drumming may lie in both musical and physical practice. As athletes, drummers could benefit the same transfer effects in cognitive tasks. Abstract: Both playing a musical instrument and playing sport produce brain adaptations that might affect sensory-motor functions. While the benefits of sport practice have traditionally been attributed to aerobic fitness, it is still unknown whether playing an instrument might induce similar brain adaptations, or if a specific musical instrument like drums might be associated to specific benefits because of its high energy expenditure. Since the aerobic costs of playing drums was estimated to be comparable to those of average sport activities, we hypothesized that these two groups might show both behavioral and neurocognitive similarities. To test this hypothesis, we recruited 48 young adults and divided them into four age-matched groups: 12 drummers, 12 athletes, 12 no-drummer musicians and 12 non-athletes. Participants performed a visuo-motor discriminative response task, namely the Go/No-go, and their cortical activity was recorded by means of a 64-channel electroencephalography (EEG). Behavioral performance showed that athletes and drummers were faster than the other groups. Electrophysiological results showed that the pre-stimulus motor preparation (i.e. the Bereitschaftspotential or BP) and attentional control (i.e., the prefrontal negativity or pN), and specific post-stimulus components like the P3 and the pP2 (reflecting the stimulus categorization process) were enhanced in the athletes and drummers' groups. Overall, these results suggest that playing sport and drums led to similar benefits at behavioral and cognitive level as detectable in a cognitive task. Explanations of these findings, such as on the difference between drummers and other musicians, are provided in terms of long-term neural adaptation mechanisms and increased visuo-spatial abilities.